The Role of the Future Career Prospects in Students’ Educational Motivation of Birjand University of Medical Sciences - M Akbari Booreng (Journal of Medical Education and Development, 2015)
Introduction : One of the important factors affecting on students’ educational success is their educational motivation. This study was designed and performed for investigating the role of the future career prospects in students’ educational motivation.   Methods : This was a cross sectional analytic study. For this purpose according to Cochrane formula, 285 participants were selected based on the random-cluster method out of all students of Birjand University of Medical Sciences in 2013-2014 academic year. The questionnaires of mental illustration of the future career and educational motivation were used to gather data. The collected data were analyzed through Structural Equation-Finding Method by using PLS software.   Results : The findings of the present study showed that the used model had a suitable fitting. All direct and indirect paths were significant and confirmed (p<0.01), but the direct path of mental illustration of the future career to demotivation. The results also revealed that the students of Anesthesiology had less motivation compared to the students of medicine, health and laboratory sciences. Moreover, the students of operating room had more extrinsic motivation than nursing students. The students of operating room had less intrinsic motivation than the students of medicine.   Conclusion : With regard to the results of this study and the role of future career prospects in the students’ educational motivation, it seemed that providing a situation for students’ mental illustration of their future career by instructors and university lecturers was necessary.